Engineering of aggregation-induced emission luminogens by isomeric strategy to achieve high-performance optoelectronic device. (February 2020) - Wen, Lili; Zang, Chunxiu; Gao, Ying; Tao, Yanli; Li, Guangfu; Shan, Guogang; Sun, Haizhu; Xie, Wenfa; Su, Zhongmin
Abstract: Achieving non-doped organic light-emitting diodes (OLEDs) with high electroluminescent (EL) performance is essential for both illumination source and display applications. A source of this difficulty is the aggregation-induce quenching effect of emitters in the solid state, which results in low EL efficiency and severe roll-off. Herein, four isomeric aggregation-induced emission luminogens (AIEgens), namely TPE-3Cz- m PBI, TPE-3Cz- p PBI, TPE-2Cz- m PBI, and TPE-2Cz- p PBI, are constructed by varying the linkage positions of electron-accepter 1, 2-diphenyl-1 H -benzo[ d ]imidazole (PBI ), electron-donor carbazole, and AIE-active triphenylethene functional groups. A comprehensive investigation is carried out, and the results indicate that position isomerism dramatically affects electronic structures, photophysical properties, carrier transport capabilities, and device performances. Compared with TPE-3Cz- m PBI and TPE-3Cz- p PBI, TPE-2Cz- m PBI, and TPE-2Cz- p PBI exhibit more excellent AIE-active with the fluorescence quantum yield up to 72.5% and 89.7% in the neat films. Moreover, TPE-2Cz- m PBI shows high electron transport property and appropriate energy level, which favor balanced charge carrier injection/transporting in OLEDs. Hence, non-doped device based on TPE-2Cz- m PBI exhibits the best EL performance with external quantum efficiency, current efficiency, and power efficiency of 3.2%, 7.8 cd A −1, and 7.7 lm W −1, respectively. The isomeric strategy presents a promising method to extend the structural diversity of highly efficient AIE emitters, optimize optoelectronic properties, and construct high-performance non-doped devices. Due to intrinsic twisted structure and accessible protonated N -electron in molecular framework, the isomers exhibit impressive mechanochromism and acidochromism. Graphical abstract: Image 1 Highlights: Four AIEgens composing triphenylethene, carbazole, and PBI groups were synthesized. The photoelectric properties of the compounds can be adjusted by isomeric strategy. The TPE-2Cz- m PBI shows high PLQY and good electron transport ability. Nondoped OLED based on TPE-2Cz- m PBI achieves CE and EQE of 7.8 cd A −1 and 3.2%. All AIEgens exhibit mechanochromism and acidochromism.